BALANCE OF POWER NUCLEAR PROLIFERATION POLICY NORTH KOREA ACCORDING TO KENNET WALTZ'S NEOREALISM PERSPECTIVE - Mas'adi, Anwar; Abdullahi, Mohammad Syauqi; Nur, Sirojudin Ibn; Hanani, Beryl Labiq (Spektrum, 2024)
Abstract            Nuclear weapons, since their emergence in 1945, have become a global cause for concern. In the realm of international politics, two primary viewpoints have arisen. Firstly, there is the perspective that supports nuclear proliferation, asserting that every nation's freedom to possess nuclear weapons can create global stability. Secondly, there is the viewpoint that opposes proliferation, with the belief that the possession of nuclear weapons should be restricted to prevent an arms race and nuclear warfare. In this context, the Nuclear Non-Proliferation Treaty (NPT) emerged in 1970 with the goal of preventing the spread of nuclear weapons and promoting the peaceful use of nuclear energy. While many countries, including the five nuclear-armed states, have joined the NPT, North Korea became a member in 1985 but later withdrew in 2003. North Korea, with its nuclear policy, has stirred international tensions. They view nuclear weapons as a tool to safeguard their sovereignty and maintain their presence in international politics. From a neorealism perspective, the concept of the balance of power becomes relevant, with concerted efforts to balance power as a means to achieve power equilibrium and prevent the dominance of superpowers. North Korea conducted a series of nuclear tests from 2006 to 2017, resulting in strong reactions from the international community, including sanctions imposed by the United Nations. North Korea believes that nuclear weapons will provide them with significant leverage and protect their sovereignty. In the context of North Korea's nuclear proliferation, the neorealism approach and the concept of balance of power offer insights into the dynamics, their influence on other nations, the responses of the international community, and their impact on global stability.Keywords: Proliferation, Nuclear, North Korea, Neorealism